You have new items in your feed. Click to view.
Q: Simplify: 3(x + 4) - 2(x - 2) a. x + 8 b. -5x + 16 c. x + 16 d. 5x + 16
A: 3(x + 4) - 2(x - 2) =3x+12-2(x-2) =3x+12-(2x-4) =x+16
Original conversation
User: Simplify: 3(x + 4) - 2(x - 2) a. x + 8 b. -5x + 16 c. x + 16 d. 5x + 16

Weegy: The answer is x=(1)/(2). [ 5-(x+2)=5x Multiply -1 by each term inside the parentheses (x+2). 5-(x)-(2)=5x Multiply -1 by the x inside the parentheses. 5-x-(2)=5x Multiply -1 by the 2 inside the parentheses. 5-x-2=5x Subtract 2 from 5 to get 3. 3-x=5x Since 5x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 5x from both sides. 3-x-5x=0 According to the distributive property, for any numbers a, b, and c, a(b+c)=ab+ac and (b+c)a=ba+ca. Here, x is a factor of both -x and -5x. 3+(-1-5)x=0 Subtract 5 from -1 to get -6. 3+(-6)x=0 Remove the parentheses. 3-6x=0 Since 3 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 3 from both sides. -6x=-3 Divide each term in the equation by -6. -(6x)/(-6)=-(3)/(-6) Move the minus sign from the denominator to the front of the expression. -(-(6x)/(6))=-(3)/(-6) Cancel the common factor of 6 in -(6x)/(6). -(-( 6 x)/( 6 ))=-(3)/(-6) Remove the common factors that were cancelled out. -(-x)=-(3)/(-6) Multiply -1 by the -x inside the parentheses. -1*-x=-(3)/(-6) Multiply -1 by -x to get x. x=-(3)/(-6) Move the minus sign from the denominator to the front of the expression. x=-(-(3)/(6)) Cancel the common factor of 3 in -(3)/(6) since -(3)/(6)=((-1*3))/((2*3)). x=-(-( 3 )/(2 6 )) Remove the common factors that were cancelled out. x=-(-(1)/(2)) Multiply -1 by the -(1)/(2) inside the parentheses. x=-1*-(1)/(2) Multiply -1 by -1 to get 1. x=(1)/(2). Hope this helps. ]
thederby|Points 1238|

Question
Updated 6/30/2014 12:55:26 AM
This conversation has been flagged as incorrect.
Flagged by jeifunk [6/30/2014 12:55:26 AM]
Rating
3
3(x + 4) - 2(x - 2)

=3x+12-2(x-2)

=3x+12-(2x-4)

=x+16

Questions asked by the same visitor
Simplify: -3(2z + 7) a. -6z + 7 b. -6z - 21 c. -6z + 21 d. -27z
Question
Updated 8/5/2014 11:43:58 PM
-3(2z + 7) = -6z - 21
Simplify: -3(2z + 7)
Weegy: -3(2z + 7) = -6z - 21 (More)
Question
Updated 5/1/2014 12:58:49 AM
Simplify: 3(x + 4) - 2(x - 2) a. x + 8 b. -5x + 16 c. x + 16 d. 5x + 16
Weegy: 3(x+4)-2(x-2)*ax+8b-5x+16cx+16dx+16 Multiply 3 by each term inside the parentheses (x+4). 3(x)+3(4)-2(x-2)*ax+8b-5x+16cx+16dx+16 Multiply 3 by the x inside the parentheses. 3*x+3(4)-2(x-2)*ax+8b-5x+16cx+16dx+16 Multiply 3 by x to get [ 3x. 3x+3(4)-2(x-2)*ax+8b-5x+16cx+16dx+16 Multiply 3 by the 4 inside the parentheses. 3x+3*4-2(x-2)*ax+8b-5x+16cx+16dx+16 Multiply 3 by 4 to get 12. 3x+12-2(x-2)*ax+8b-5x+16cx+16dx+16 Multiply -2 by each term inside the parentheses (x-2). 3x+12-2(x)-2(-2)*ax+8b-5x+16cx+16dx+16 Multiply -2 by the x inside the parentheses. 3x+12-2*x-2(-2)*ax+8b-5x+16cx+16dx+16 Multiply -2 by x to get -2x. 3x+12-2x-2(-2)*ax+8b-5x+16cx+16dx+16 Multiply -2 by the -2 inside the parentheses. 3x+12-2x-2*-2*ax+8b-5x+16cx+16dx+16 Multiply -2 by -2 to get 4. 3x+12-2x+4*ax+8b-5x+16cx+16dx+16 Multiply 4 by ax to get 4ax. 3x+12-2x+4ax+8b-5x+16cx+16dx+16 According to the distributive property, for any numbers a, b, and c, a(b+c)=ab+ac and (b+c)a=ba+ca. Here, x is a factor of both 3x and -2x. (3-2)x+12+4ax+8b-5x+16cx+16dx+16 To add integers with different signs, subtract their absolute values and give the result the same sign as the integer with the greater absolute value. In this example, subtract the absolute values of 3 and -2 and give the result the same sign as the integer with the greater absolute value. (1)x+12+4ax+8b-5x+16cx+16dx+16 Remove the parentheses. x+12+4ax+8b-5x+16cx+16dx+16 According to the distributive property, for any numbers a, b, and c, a(b+c)=ab+ac and (b+c)a=ba+ca. Here, x is a factor of both x and -5x. (1-5)x+12+4ax+8b+16cx+16dx+16 To add integers with different signs, subtract their absolute values and give the result the same sign as the integer with the greater absolute value. In this example, subtract the absolute values of 1 and -5 and give the result the same sign as the integer with the greater absolute value. (-4)x+12+4ax+8b+16cx+16dx+16 Remove the parentheses. -4x+12+4ax+8b+16cx+16dx+16 Add 16 to 12 to ... (More)
Question
Updated 6/24/2012 11:10:49 PM
c. x + 16

3(x + 4) - 2(x - 2) = 3x + 12 - 2x + 4 = x + 16.

Source:
Rated bad by John@evang, Confirmed by jeifunk [6/30/2014 12:54:32 AM]
Sorry for the error.
This answer has been flagged as incorrect.
Flagged by jeifunk [6/30/2014 12:53:41 AM]
Ans-C: x + 16 =
3(x+4)-2(x-2)=
3x + 12 - 2x + 4=
collect the like terms.
3x - 2x + 12 + 4=
x + 16 .
This answer has been flagged as incorrect.
Confirmed by jeifunk [6/30/2014 12:54:19 AM], Unconfirmed by jeifunk [6/30/2014 12:54:28 AM], Flagged by jeifunk [6/30/2014 12:54:34 AM], Unflagged by jeifunk [6/30/2014 12:54:45 AM], Flagged by jeifunk [6/30/2014 12:54:48 AM]
c 3x+12-2x+4=x+16
This answer has been flagged as incorrect.
Flagged by jeifunk [6/30/2014 12:54:38 AM]
Combine like terms: 4x + 2y - 3x + 7y
Weegy: 4x + 2y - 3x + 7y = x + 9y (More)
Question
Updated 4/28/2014 4:49:02 PM
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 230 [Total 248] Ratings 0 Comments 160 Invitations 7 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
L
R
Points 105 [Total 256] Ratings 1 Comments 5 Invitations 9 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 60 [Total 13327] Ratings 0 Comments 60 Invitations 0 Online
S
L
1
R
Points 31 [Total 1447] Ratings 2 Comments 11 Invitations 0 Offline
S
Points 20 [Total 20] Ratings 1 Comments 0 Invitations 1 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.